Financial Village Management Predictors with Work Motivation as a Moderating Factor - Susilowati, Nurdian; Mulyono, Maya Diantari; Mahmud, Amir; Sari, Puji Novita (Jurnal ASET (Akuntansi Riset), 2024)
This research aims to analyze the impact of village apparatus competence (VAC), organizational commitment (OC), and the whistleblowing system (WS) on village financial management (VF), with work motivation (WM) as a moderating variable. This research is quantitative and uses a causal approach. The populations of this research are village official in Sragi District, with a total sample of 112 respondents. The sampling technique used is purposive sampling. Data were analyzed using descriptive and moderation regression analysis (MRA) with the SmartPLS analysis tool. The research results show that village apparatus competence, organizational commitment, and the whistleblowing system have affects on village financial management. Work motivation can moderate and strengthen the relationship between organizational commitment and village financial management. Besides, it does not strengthen the relationship between whistleblowing on village financial management. This research makes a valuable contribution to the accounting field, particularly in the context of public sector organizations, by applying Stewardship theory. It applies the relationship of collaboration between the steward and the principal to accomplish the village's objectives. The orisinality of this research lies in the incorporating of a whistleblowing system and work motivation as the moderation factors.